Measuring perceived service quality using SERVQUAL model : a case study of TH Hotel Kota Kinabalu / Muhammad Benyamin Arieff Abdul Latif - Abdul Latif, Muhammad Benyamin Arieff (2016)
This research is an attempt to investigate the customer's perceived service quality in TH Hotel Kota Kinabalu. Over 300 questionnaires were distributed during the study. The researcher identified that there are five (5) independent variables which is the SERVQUAL involved in this study namely Responsiveness, Tangibles, Reliability, Assurance and Empathy. In the findings, it is shown that Responsiveness has an insignificant relationship with the dependent variable which can be determine as weakest dimensions and need to be improve. The dependent variable in this study is the customer's perceived service quality in TH Hotel Kota Kinabalu. Respondent involved in this study are among walk in customer who are happens to be the customer of TH Hotel Kota Kinabalu.